2016
DOI: 10.1002/2015jg003027
|View full text |Cite
|
Sign up to set email alerts
|

Summer storms trigger soil N2O efflux episodes in forested catchments

Abstract: Climate change and climate-driven feedbacks on catchment hydrology and biogeochemistry have the potential to alter the aquatic versus atmospheric fate of nitrogen (N) in forests. This study investigated the hypothesis that during the forest growth season, topography redistributes water and water-soluble precursors (i.e., dissolved organic carbon and nitrate) for the formation of gaseous N species. Soil nitrous oxide (N 2 O) and nitrogen (N 2 ) efflux and soil physical and chemical properties were measured in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Topography interacts with landscape hydrology to influence carbon (C) and N biogeochemical cycling. Hot spots of N 2 O emissions have been observed in convergent hydrological flow paths due to high moisture and low O 2 concentration in the soil, favoring N 2 O production via denitrification (Enanga et al, 2016;Izaurralde et al, 2004;Pennock et al, 1992;Saha et al, 2017;Vilain et al, 2010). The hot moments are brief temporal windows with emissions that are substantially higher than the background level emission (Groffman et al, 2009;McClain et al, 2003;Molodovskaya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Topography interacts with landscape hydrology to influence carbon (C) and N biogeochemical cycling. Hot spots of N 2 O emissions have been observed in convergent hydrological flow paths due to high moisture and low O 2 concentration in the soil, favoring N 2 O production via denitrification (Enanga et al, 2016;Izaurralde et al, 2004;Pennock et al, 1992;Saha et al, 2017;Vilain et al, 2010). The hot moments are brief temporal windows with emissions that are substantially higher than the background level emission (Groffman et al, 2009;McClain et al, 2003;Molodovskaya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The soil pore water DOC and NO 3 − concentrations varied among the topographic positions, which provides further insight into the processes generating N 2 O. The DOC and NO 3 − accumulated at the UP position, which may suggest that denitrification was limited by high redox conditions, as is observed during the growing season [ Enanga et al ., ; Kralova et al ., ], but that the NO 3 − pools were maintained through nitrification. In contrast, DOC and NO 3 − did not accumulate in the wetland positions, suggesting that denitrification may be limited by nutrient conditions beneath a snowpack in the wetland.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work investigated topographic controls on dissolved N export, including NO 3 − , ammonium, and dissolved organic nitrogen [ Creed and Beall , ; Creed and Band , ; Creed and Band , ]. A related study investigated the physical and chemical controls on biological N transformations within forested catchments during the growing season and observed that precipitation triggered changes in redox conditions in wetland soils that resulted in net soil N 2 O production events [ Enanga et al ., ]. This study builds on this work by providing new insights into gaseous N exports during the nongrowing season including the snow period.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the IW position may have been influenced by a hydrological ''decoupling'' between surface and subsurface processes during a rain event, especially in late summer/early fall when water table depths typically drop well below the surface. It is possible that the rain triggers soil CO 2 efflux events by creating optimal conditions that include delivery of fresh substrate from rain passing through the canopy to sedentary soil microbes, in addition to providing optimal temperature and moisture conditions for microbial respiration (e.g., Enanga et al 2016). Further, labile carbon-laden water in the uplands would tend to flow rapidly downslope through surface and shallow subsurface flowpaths during a rain event, increasing carbon pools in the FS and TS positions especially on steeper transects (Riveros-Iregui and McGlynn 2009).…”
Section: Discussionmentioning
confidence: 99%